Education in Human Rights in Spain - José Tuvilla Rayo (ADIDE Federación, 2008)
The next Dec. 10 is celebrated the 60th anniversary of the Universal Declaration of Human Rights, proclaimed by the UN General Assembly, starting from that date, the International Year for Human Rights Learning. For this reason, this article aims to recover the memory of the teaching unfinished road in our country, education for peace and human rights from its beginnings until today. And to do both from the experience as a recognition of the individual, collective and legal guidance which has enabled and define a set of ideas relating to force or allow us to understand its current state. No doubt that in this trip, will be without citing some experiences, to be recovered by others and those others who directly or indirectly involved and understand the value thereof. The reader should forgive and forget this fledgling complete this study. To do this, my most sincere invitation to write the history of human rights education as an avenue of research little edge, and yet so important to future generations. Who so decides, in this article some initial notes, and in some cases, small items marked, a narrative constructed collectively.